ELEP Students' Experiences in Reading English Journal Articles: Do they Have Difficulties? - Saputri, Siska; Fudhla, Nora (Journal of English Language Teaching, 2024)
English Language Education Program (ELEP) students at Universitas Negeri Padang are burdened with complex English journal articles. This research investigates the difficulties and factors influencing their comprehension of these demanding texts and dominant difficulties and factors. This research uses a descriptive qualitative approach; the research involved 96 participants who answered the questionnaire and two from each class for in-depth interviews. The results of this research showed that are seven main factors contributing to students' difficulties: Difficulty understanding idea, Main idea, Supporting idea, Complicated sections of English journal article, Concluding English journal article, Topic-related vocabulary/technical terms/ difficult words, Inability to read quickly to find information, Complex language style and sentence structure, and challenging topics. Among these difficulties, vocabulary problems emerged as the most dominant aspect, posing a significant barrier to comprehension. In particular, the research identified an emerging trend of over-reliance on translation tools that hinders independent comprehension. The findings have valuable implications for future research, directing efforts to increase students' interest in reading English journal articles and developing effective strategies to overcome vocabulary challenges. By addressing these underlying issues, we can empower ELEP students to navigate the world of English academic literature confidently.